If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying N + -13 = -18 Reorder the terms: -13 + N = -18 Solving -13 + N = -18 Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + N = -18 + 13 Combine like terms: -13 + 13 = 0 0 + N = -18 + 13 N = -18 + 13 Combine like terms: -18 + 13 = -5 N = -5 Simplifying N = -5
| -3(1-7n)=-31-7n | | 25*(5)525-66=5 | | -6(6r+3)+5(r+5)=69 | | 5x+18=6x+14 | | x+132=125 | | 6(2+6k)-8=-176 | | -(b-5)=b-3 | | -3(-2+x)=-10 | | -11+a=-2(7a-2) | | 19r=-57 | | x^2+(1-i)x-i=0 | | -4v+2(-1-6v)=-130 | | -2(2y-6)-y=-2(y-3) | | 2a-4=3(a-4) | | x^2+(1-i)x-1=0 | | 2(2y-1)=-19 | | -32+8v=6(v-7) | | 2b^2+3b-2= | | -42=3(6+8b)+6(-3b-7) | | 9x-2=133 | | 60=-5(6n-6) | | 38-n=5+4(-2n+3) | | -26+6p=-8(1-3p) | | 2(r+4)=-35 | | 580=-20b | | 9y+12=84 | | 21x-3=40x | | 2(3-x)=60 | | -5.5=-3.4 | | 7(x-2)=5(x-4) | | -7(7n+7)=39-5n | | 3+r=19 |